HP gaming - Isaacs, Andrew M., (SAGE Knowledge. Cases., 2017)
This case study focuses on how a large company, Hewlett-Packard (HP) works through the strategic, branding, and organizational issues related to its new acquisition, VoodooPC. The case addresses some key issues related to acquisitions, especially how a large established company like HP navigates the sometimes complicated road of integrating a small, yet successful brand like VoodooPC.